2005
DOI: 10.1007/s10517-005-0367-2
|View full text |Cite
|
Sign up to set email alerts
|

Inotropic Response of the Myocardium in Rats with Postinfarction Cardiosclerosis Exposed to Extrasystolic Treatment

Abstract: The inotropic response of the myocardium to extrasystolic treatment was studied on isolated perfused papillary muscles from rats with postinfarction cardiosclerosis. The development of postinfarction cardiosclerosis was accompanied by a decrease in myocardial excitability. The amplitude of extrasystolic contractions in the remodeled myocardium far surpassed the control. However, the amplitude of postextrasystolic contraction did not surpass that in normal contraction-relaxation cycle. Our results suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…According to published reports and our data ( Fig. 1), dead cardiomyocytes are replaced with the connective tissue and a scar is formed in the zone of necrosis 40 days after this procedure; heart hypertrophy develops [4].…”
Section: Methodssupporting
confidence: 63%
See 2 more Smart Citations
“…According to published reports and our data ( Fig. 1), dead cardiomyocytes are replaced with the connective tissue and a scar is formed in the zone of necrosis 40 days after this procedure; heart hypertrophy develops [4].…”
Section: Methodssupporting
confidence: 63%
“…Experiments were carried out on male Wistar rats weighing 180-230 g. Damage to the myocardium was induced by coronary occlusion [4]. The thorax and the pericardium were opened under light ether anesthesia and a ligature was applied on the upper third of the left descending coronary artery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Our previous studies [1] showed that the rat cardiomyocyte excitability reduced in PICS, the PEC amplitude not depending on the degree of extrasystolic contraction. Our present findings indicate that muscle strips from postinfarction myocardium do not react to extrasystolic exposure by potentiation.…”
Section: Resultsmentioning
confidence: 87%
“…On day 45 after coronary occlusion, postinfarction cardiosclerosis (PICS) developed. Similar coronary occlusion procedure was described elsewhere [3,8].…”
Section: Methodsmentioning
confidence: 99%